SEMANTIC ANALYSIS OF SLANG VARIETIES BY GEN Z IN TIKTOK APPLICATION - Amelia Febrianti; Yeni Rakhmawati Agustin; Dea Putri Pascha F; Adinda Rusdianti; Endang Sholihatin (Media Inovasi Pendidikan dan Publikasi, 2023)
The slang used by gen Z in the TikTok application is related to the development of communication technology which causes the development of the language used in society, both oral and written. One of the impacts of these developments is the emergence of language variations that are often referred to as slang. The language used in TikTok often comes from the songs in the videos uploaded on the platform and is used to communicate. The use of slang on TikTok has led to the emergence of various types of slang, which continue to change and develop over time. This study aims to analyze the semantics of the variety of slang used by gen z on the TikTok application with a qualitative approach. Qualitative methods are used to further explore the meaning, context, and language variations used in their content. qualitative methods where a problem formulation guides research to explore the social situation to be studied thoroughly, broadly and in depth. This research is strengthened by interviews with gen z who often use the Tiktok application, is there an influence on the variety of language used in communication.